Prevalence and Association of LPA Gene Variant the Statin Therapeutic Response in Cardiovascular Patients - Zakia Shafqat, Shagufta Naz, Muhammad Akram Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Cardiac patients who fail to achieve critical biochemical parameters are considered as resistant. Differences in drug absorption, transport, in trapeutic drug metabolism, drug metabolism in other organs, and drug excretion mechanisms can all be linked to tatin resistance. Numerous single nucleotide polymorphisms (SNPs) have been discovered in the solute carrier organic transporter LPA gene, with three common SNPs labelled as 872G> A, 220 T>C and 384 A>G which are thought to be the most common and responsible for the LPA transporter’s suitable transport function. Method: Cardiac patients (Both Males and Females i.e. n=90) who were on statin therapy from last one year were engaged to evaluate the statin treatment response. DNA was extracted from blood samples of all cardiac patients in the study. To amplify the targeted region of SNPs of gene LPA, an allele specific PCR extension was performed. Allele specific extension based PCR products for three SNPs were electrophoresed on agarose gel to find out the possible variant in each patient. To validate gel-based identified genotypes, selected PCR products for possible allelic variants of each genetic marker were sequenced using the Sanger’s Sequencing method. Results: For SNP (rs104455872), the genotype GA (66.6%) was found to be the most frequent genotype in comparison to genotype AA (20%) and GG (13.3%) in this study group. Similarly, for genetic marker (SNP rs3798220) the genotype frequencies of genetic variant TC (70%), is higher as compared to other genotypes TT (13.30%), CC (16.6%). For genetic marker rs 74617384) AG was found higher in the genotype AG (83.3%) in comparison to other genotype GG (10%) to other minor allele. In overall cardiac patients, the rosuvastatin was prescribed to more cardiac patients (55.17%) than the atorvastatin (44.83%). The genotype GA (rs104455872) was more frequently prescribed rosuvastatin by the physician (36.3%) in comparison to atorvastatin (30%) for the same genotype GA. All other two genotypes of marker rs104455872 were least frequently prescribed with both statin salts (rosuvastatin & atorvastatin). Similarly, the genotype TC of marker, (rs3798220), was more frequently prescribed rosuvastatin by the physician (43.3%) in comparison to atorvastatin (26.6%) for the same genotype TC. The genotype TT of marker, rs3798220, found rarely prescribed by both statin salts i.e. rosuvastatin (0.0%) & atorvastatin (3.4%). The genotype AG (rs74617384) was more frequently prescribed rosuvastatin by the physician (46.6%) in comparison to atorvastatin (36.6%%) for the same genotype AG. All other three genotypes of marker rs2306283 were least frequently prescribed with both statin salts (rosuvastatin& atorvastatin). Conclusions: The genotyping of cardiac patients for the genetic markers (rs 104455872), (rs3798220)or (rs 74617384)) of gene LPA gene may be helpful to tailor the statin salt for precision therapy and may reduce the adverse effects in cardiac patients. Keywords: Single nucleotide polymorphism, lipoprotein particle A, Hydroxy methyl glutarate co enzyme A, Statin Associated Muscle Symptoms, LDL-C, HDL-C